Large Hexagonal Bi‐ and Trilayer Graphene Single Crystals with Varied Interlayer Rotations1. Issue 6 (22nd January 2014) - Yan, Zheng; Liu, Yuanyue; Ju, Long; Peng, Zhiwei; Lin, Jian; Wang, Gunuk; Zhou, Haiqing; Xiang, Changsheng; Samuel, E. L. G.; Kittrell, Carter; Artyukhov, Vasilii I.; Wang, Feng; et al.
Abstract Bi‐ and trilayer graphene have attracted intensive interest due to their rich electronic and optical properties, which are dependent on interlayer rotations. However, the synthesis of high‐quality large‐size bi‐ and trilayer graphene single crystals still remains a challenge. Here, the synthesis of 100 μm pyramid‐like hexagonal bi‐ and trilayer graphene single‐crystal domains on Cu foils using chemical vapor deposition is reported. The as‐produced graphene domains show almost exclusively either 0° or 30° interlayer rotations. Raman spectroscopy, transmission electron microscopy, and Fourier‐transformed infrared spectroscopy were used to demonstrate that bilayer graphene domains with 0° interlayer stacking angles were Bernal stacked. Based on first‐principle calculations, it is proposed that rotations originate from the graphene nucleation at the Cu step, which explains the origin of the interlayer rotations and agrees well with the experimental observations.